Dimensi Good Corporate Governance pada Kinerja Pasar Perusahaan Otomotif - Sinaga, Fritz Basar Miguel; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 33 No 5 (2023)DO - 10.24843/EJA.2023.v33.i05.p06, 2023)
Capital market performance is the overall cumulative performance resulting from the overall performance of each share listed and traded on the Indonesia Stock Exchange. This study aims to examine the influence of the dimensions of Good Corporate Governance on the market performance of automotive companies listed on the Indonesia Stock Exchange. This research is a quantitative research using secondary data obtained from financial reports and annual reports on the automotive sub-sector companies and their components. The sampling technique used a purposive sampling technique that selected 12 sample companies that met predetermined criteria. Hypothesis testing using multiple linear regression analysis. The results of the study show that managerial ownership, independent commissioners, audit committees, and institutional ownership have a significant effect on the performance of the automotive market listed on the Indonesia Stock Exchange. The better the GCG proportion of a company will also give a good picture in the eyes of investors, thereby increasing the trust and value of the company. Keywords:  Managerial Ownership; Independent Board of Commissioners; Audit Committee; Institutional Ownership; Market Performance